Political dynasties and their influence on foreign direct investments the case of the Philippines - Lapitan, Almira Grace R.; Reyes IV, Juan Mauro Iñigo R.; Solon, Orville Jose C. (Quezon City School of Economics, University of the Philippines Diliman, 2022)
This study examines if there is a link between political dynasties and foreign direct investment in the Philippines. Previous studies have shown that dynastic presence negatively affects various economic measures, and this study finds that the relationship generally holds for foreign direct investment as well. Most notably, this relationship applies to fat-tailed dynasties and vertically-linked politicians; trade openness is also found to be a significant determinant of FDI. The researchers use a fixed-effects multiple linear regression model and employ different dynastic measures to evaluate not only whether dynasties affect foreign investment but also what kinds of dynasties may do so. Due to data availability concerns and Capuno's (2005) regional development disparity as a basis, a provincial-level analysis is utilized; the data used ranges from 2003 to 2021.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Political dynasties -- Philippines; Foreign direct investment -- Philippines; Political corruption -- Philippines; Politics and government -- Economic aspects -- Philippines